2017
DOI: 10.1177/1591019917722514
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline embolization device retraction and foreshortening after internal carotid artery blister aneurysm treatment

Abstract: Background Subarachnoid hemorrhage (SAH) secondary to rupture of a blister aneurysm (BA) results in high morbidity and mortality. Endovascular treatment with the pipeline embolization device (PED) has been described as a new treatment strategy for these lesions. We present the first reported case of PED retraction and foreshortening after treatment of a ruptured internal carotid artery (ICA) BA. Case description Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Poor wall attachment plays a significant role in the treatment of complex lesions, including immediate and delayed stent displacement or retraction ( Brinjikji et al, 2016 ; Heit et al, 2017 ). When this occurs, salvage of failed PED treatment is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Poor wall attachment plays a significant role in the treatment of complex lesions, including immediate and delayed stent displacement or retraction ( Brinjikji et al, 2016 ; Heit et al, 2017 ). When this occurs, salvage of failed PED treatment is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…ICA bifurcation is an uncommon location for a PED. To avoid PED retraction after treatment, it is necessary to deploy the end of the PED in the M1 segment and cover the origin of A1 [6,[9][10][11]. Sufficient preoperative evaluation is required for this off-label use, and previous reports have shown that approximately 2/3 of arteries covered by a flow diverter will become stenotic or occluded during follow-up [2].…”
Section: Discussionmentioning
confidence: 99%
“…The resolution of the vasospasm 15 days after endovascular therapy was mostly due to the increased diameter of the basilar trunk with delayed poor wall apposition of the FD and readmission of the patient to hospital due to occlusion of the perforating branches demonstrated by MRI. Since retraction of FDs in ruptured aneurysms has already been described in the literature,18 19 the identification of the exact timing of symptom onset, the appropriate timing of rPCPA treatment, intra-arterial infusion of nimodipine from the guide catheter as well as FD oversizing may reduce the risk of this ischemic complication in future.…”
Section: Discussionmentioning
confidence: 99%